The Legal Protection of Children's Rights due to Parental Divorce in Islamic Family Law in Predominantly Muslim Countries - Budi Prasetyo; Haitham Abdulwahhab Mohammed B. (JURNAL AKTA, 2023)
The divorce is a legal event whose consequences are regulated by law. According to Islamic Family Law, it is considered as legal event that has legal consequences for both couple and the children. Many Islamic countries has specified the consequence of divorce law for the legal protection of children as that both fathers and mothers must still maintain and educate their children. Now, their legal systems have extended the interests of the child in both regulations and court decisions. The issue of legal protection for children and the obligations of parents to children has been regulated in various laws and regulations in some Islamic countries. Court decisions obliged the parents to fulfill children's rights as a form of legal protection for children. The purpose of this study is to investigate the legal protection of children due to parental divorce in some Islamic countries. The object for the research was the regulations in the form of Islamic Family Law in Indonesia, Malaysia and Bangladesh. The method is normative juridical with library research technique by analyzing legal documents in the forms of legal literature, regulations or legislation. The findings of this study highlight the role of decision makers and related institutions to strengthen the magnitude of family law and human rights in providing legal protection for children. The findings are desirable to become a practical and theoretical reference in synchronizing the interests between justice values and the need for family law reconstruction to fulfil children’s interests in parental divorce cases.